2019
DOI: 10.1089/neu.2018.5829
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Acute Subdural Hematoma in the Elderly: A Systematic Review

Abstract: Acute subdural hematoma (aSDH) is among the most common injury types encountered by neurosurgeons, and carries a poor prognosis, particularly in the elderly. As the incidence of aSDH in the elderly population rises, identifying those patients who may benefit from operative intervention is crucial. This systematic review aimed to identify data on prognostic factors or indices, such as the modified frailty index, that may help predict outcome, and hence guide management. A comprehensive search of online database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 40 publications
3
31
0
2
Order By: Relevance
“…A systematic review into the prognosis of ASDH in the elderly demonstrated that the mechanism of injury was not a predictor of mortality. 18) Although another study found that injuries caused by traffic accidents were associated with poor outcomes, as this study was performed 37 years ago, 19) its findings may no longer be accurate.…”
Section: Discussionmentioning
confidence: 82%
“…A systematic review into the prognosis of ASDH in the elderly demonstrated that the mechanism of injury was not a predictor of mortality. 18) Although another study found that injuries caused by traffic accidents were associated with poor outcomes, as this study was performed 37 years ago, 19) its findings may no longer be accurate.…”
Section: Discussionmentioning
confidence: 82%
“…Prognosis of ASDH, particularly in the elderly, was evaluated in a systematic review that included seven eligible studies. The researchers investigated the predictive factors and modified index and they found that an initial GCS of 3-8 was the most important predictive factor for a negative outcome (18). In a retrospective study focusing on the criteria for surgery in elderly patients with ASDH, a GCS of 3-8 was a significant indicator for high mortality (P<0.001) (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, older age is generally accepted to be an important predictor of poor prognosis and mortality of SDH, which has a mortality rate ranging from 35% to 80%. [19][20][21][22] Furthermore, craniotomy under general anesthesia is often inappropriate in elderly patients due to their systemic comorbid burdens, such as cardiopulmonary failure, diabetes mellitus, and the use of antithrombotic drugs. Therefore, an endoscopic procedure under local anesthesia would be useful for patients with ASDH who cannot undergo craniotomy under general anesthesia.…”
Section: Elderly Patients With Asdhmentioning
confidence: 99%